Dominican Republic : 2022 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2022)
As in the past, the Dominican Republic's dynamic economy continued to show remarkable resilience to shocks, rebounding strongly from the impact of the pandemic. Sound policies, a nimble vaccination campaign and a well-attuned reopening-including international travel-allowed the economy to make the most of the global rebound. The recovery has been broad based; GDP was about 5 percent above pre-pandemic levels as of end-2021. The country maintained sound market access and benefitted from Fund support through the Rapid Financing Instrument (RFI).